Development of Inducible Systems To Engineer Conditional Mutants of Essential Genes of Helicobacter pylori - Boneca, Ivo G. (American Society for Microbiology (ASM), 2008)
The Escherichia coli-Helicobacter pylori shuttle vector pHeL2 was modified to introduce the inducible LacI(q)-pTac system of E. coli, in which the promoters were engineered to be under the control of H. pylori RNA polymerase. The amiE gene promoter of H. pylori was taken to constitutively express the LacI(q) repressor. Expression of the reporter gene lacZ was driven by either pTac (pILL2150) or a modified version of the ureI gene promoter in which one or two LacI-binding sites and/or mutated nucleotides between the ribosomal binding site and the ATG start codon (pILL2153 and pILL2157) were introduced. Promoter activity was evaluated by measuring β-galactosidase activity. pILL2150 is a tightly regulated expression system suitable for the analysis of genes with low-level expression, while pILL2157 is well adapted for the controlled expression of genes encoding recombinant proteins in H. pylori. To exemplify the usefulness of these tools, we constructed conditional mutants of the putative essential pbp1 and ftsI genes encoding penicillin-binding proteins 1 and 3 of H. pylori, respectively. Both genes were cloned into pILL2150 and introduced in the parental H. pylori strain N6. The chromosomally harbored pbp1 and ftsI genes were then inactivated by replacing them with a nonpolar kanamycin cassette. Inactivation was strictly dependent upon addition of isopropyl-β-d-thiogalactopyranoside. Hence, we were able to construct the first conditional mutants of H. pylori. Finally, we demonstrated that following in vitro methylation of the recombinant plasmids, these could be introduced into a large variety of H. pylori isolates with different genetic backgrounds.